SU93. Targeted Treatment of a Genetic Mutation in Glycine Decarboxylase With d-Cycloserine in Psychotic Disorders. (20th March 2017) - Levy, Deborah; Coleman, Michael; Godfrey, Laura; Morgan, Charity; Sebat, Jonathan; Ongur, Dost; McCarthy, Shane; Malhotra, Dheeraj; Vuckovic, Alexander; Smith, Kamiell; Kirchhoff, Colette; Suckow, Raymond; et al.
Abstract: Background: The identification of mutations in specific genes could enable personalized, "medically actionable" treatment interventions. We identified a potentially informative mutation, a rare structural rearrangement that includes a triplication of the glycine decarboxylase gene (GLDC). GLDC is the enzyme that catabolizes glycine, a precursor of d -serine, both of which are coagonists at the NMDA receptor (NMDAR). Four copies of GLDC would be expected to increase the degradation of glycine, resulting in low levels of brain glycine and NMDAR-mediated hypofunction, which has been strongly implicated in the pathophysiology of psychotic disorders. Carriers of this mutation may especially benefit from augmentation of psychotropic drug treatment with NMDAR coagonists. Methods: We carried out a double-blind placebo-controlled clinical trial (6 weeks per arm) of d -cycloserine (DCS), a partial agonist at the NMDAR glycine site, followed by 24 weeks of open-label DCS, in 2 related individuals who are carriers of the GLDC mutation, one with a diagnosis of bipolar disorder with psychotic features and the other with a diagnosis of schizo-affective disorder. Clinical assessments were carried out every 2 weeks using the PANSS, BPRS, YMRS, HAM-D, and CGI. The same individuals previously completed trials of acute and chronic glycine augmentation, which produced significant symptom improvement but caused problematic GI side effects. Results: Full trial results are still pending as the blind has not yet been broken. However, blinded analyses show significant changes in severity of clinical symptoms, indicating that DCS either produced dramatic clinical improvements or worsened symptom severity. Complete, unblinded results will be available and presented at the meeting. Conclusion: DCS may be an effective augmentation in psychotic individuals selected for being carriers of duplications or triplications of GLDC, or who are carriers of other genetic variants resulting in NMDAR hypofunction. If DCS reduced symptom severity, it is a preferable alternative to glycine as a targeted treatment in light of its clinical efficacy, ease of administration, and favorable side effect profile.